The effect of Clerodendrun inerme (L)Gaetn on some biological aspects of Rhipicephalus turanicus Pomerantzev (Acari:lxodidae) - Mohammed R. Annor; Abeer A. Ashour (Al-Qadisiyah Journal of Pure Science, 2018)
The current study include the investigation of the impact of leaves extracts of Clerodendrum inerma( L).Garten organic solvent(Ethy alcohol, Ethy acetate, Hexan)and crud secondary compound (Terpenoid, Phenolic) on the immature and adult stage of the ticks Rhipicephalus turanicus under lab conditions, the mortality rates of Eggs and larvae after exposure to different contraction to the three solvent extract %100 . the mortarty of non-feeder nymphs reached 66.14% ,90.52% , 100%, and feeder nymphs reached %61.22 -%78.33%-81.04at concentration 60 mg\ml , adult stage non-feeder males 52.77%-63.93%-68.85%, and feeder males reached 50.77%-59%-66.14% while the mortality rates of non-engorge females reached-%45 %52.77%66.14 . and the engorge females reached%50.85-%45-%30.99 after exposur to previously mentioned extract at the same concentration respectively. The all result refer Hexan extracts are more effective than Ethyle acetate and Ethyalcohol.   Study finding revealed that the terpenoid crud extracts are more effective on the immature and adult stage mortality followed by the phenolic crud extract. The eggs and larvae mortality in terpenoid and phenolic extracts were% 100 at various concentrations .while the mortality rates of non- feeder nymphs reached 90%-39.23%,and feeder nymphs mortality reached90.52%-35.12% at previously mentioned extracts, the mortality rates of non-feeder males reached%81.04- 35.21%,and feeder males 66.14%-28.77%. males . while the mortality rates of non-engorge and engorge decreased to 45%-28.77% and 41%-21.14% in Terpenoid and Phenolic crud extracts at concentration 60 mg/ml.demonstrate from result males more aptitude to impress in Terpenoid and Phenolic crud extracts.